CSF Beta-amyloid 1–42 Concentration Predicts Delirium Following Elective Arthroplasty Surgery in an Observational Cohort Study. Issue 6 (June 2019) - Cunningham, Emma L.; McGuinness, Bernadette; McAuley, Daniel F.; Toombs, Jamie; Mawhinney, Tim; O'Brien, Seamus; Beverland, David; Schott, Jonathan M.; Lunn, Michael P.; Zetterberg, Henrik; Passmore, Anthony P.
Abstract : Objective: To test the hypothesis that APOE ε4 status and cerebrospinal fluid (CSF) Aβ42, T-tau and P-tau would independently predict the risk of postoperative delirium. Background: Delirium following surgery is common and associated with adverse outcomes. Age and cognitive impairment are consistent risk factors for postoperative delirium. Methods: This observational cohort study recruited 282 participants aged 65 years or older, without a diagnosis of dementia, admitted for primary elective hip or knee arthroplasty. Cognitive tests were undertaken preoperatively, blood and CSF were sampled at the time of spinal anesthesia, and participants were assessed daily postoperatively for delirium. Results: Increasing age ( P = 0.04), preoperative comorbidity ( P = 0.03), type of surgery ( P = 0.05), intravenous opioid usage ( P = 0.04), and low CSF Aβ42 ( P < 0.01) were independent predictors of postoperative delirium. Conclusions: This study is the first to show an independent association between CSF Aβ42 and delirium incidence in an elective surgical population, suggesting that postoperative delirium may indicate incipient Alzheimer disease. Abstract : Supplemental Digital Content is available in the text